Horizontal and vertical coordination and integration of subjects of the department of applied economy (Economic Structure) in the 1st, 2nd, 3rd and 4th courses of Degree in Tourism at the University of Malaga - García-Pozo, Alejandro (My University, 2017)
The Department of Applied Economics (Economic Structure) of the University of Malaga has its headquarters in the Faculty of Economics, although its professors teach in six centers of our University. We intend to develop the proposed project, specifically in the Faculty of Tourism where we have actually assigned six subjects in the four courses of the degree in Tourism. After five years of implementation of the new curricula in Tourism, it seems appropriate to carry out a process of horizontal and vertical coordination and integration of the contents of the subjects taught by the department's professors. The main objectives to be achieved with this project in its two years have been: first, to improve the quality of the contents of the subjects of the degree, which in some cases may have overlapped in part. Second, to equip the set of subjects of our department in the Faculty of Tourism of the horizontal and vertical coherence, that is necessary.
Keywords: Educación; Turismo